1992
DOI: 10.1021/ma00034a031
|View full text |Cite
|
Sign up to set email alerts
|

Azo polymers for reversible optical storage. 1. Poly[4'-[[2-(acryloyloxy)ethyl]ethylamino]-4-nitroazobenzene]

Abstract: ethyl]ethylamino]-4-nitroazobenzene] (pDRIA) is used as an example to demonstrate the ability of amorphous high-Tg azoaromatic-containing polymers to reversibly store optical information. Writing, reading, erasing, and rewriting processes are performed using laser beams on a pDRIA film. This ability is based on the well-known trans-cis-trans isomerization process which was previously studied on liquid-crystalline polymers containing azoaromatic groups. Liquid crystallinity is not a necessary condition for opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
290
2
8

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 467 publications
(308 citation statements)
references
References 15 publications
8
290
2
8
Order By: Relevance
“…Diffraction gratings recorded while using an intensity or polarization modulated pattern ͑from now on, intensity and polarization gratings, respectively͒ and the appearance of relief gratings have been observed in these materials by using coherent light in the region of 500 nm. [1][2][3][4][5][6] A biphotonic process was found in azobenzene polyesters which can be useful in holographic experiments. 7,8 In this case, the holographic grating was written by an argon laser beam and was developed using a red He-Ne laser beam.…”
Section: ͓S0003-6951͑00͒02436-0͔mentioning
confidence: 99%
“…Diffraction gratings recorded while using an intensity or polarization modulated pattern ͑from now on, intensity and polarization gratings, respectively͒ and the appearance of relief gratings have been observed in these materials by using coherent light in the region of 500 nm. [1][2][3][4][5][6] A biphotonic process was found in azobenzene polyesters which can be useful in holographic experiments. 7,8 In this case, the holographic grating was written by an argon laser beam and was developed using a red He-Ne laser beam.…”
Section: ͓S0003-6951͑00͒02436-0͔mentioning
confidence: 99%
“…al. [35] have proposed a biexponential kinetic process in their azobenzene systems.We have also found that the biexponential functions describes the dynamics of growth and decay of refractive index changes su±ciently well in our polymers. The biexponential functions are:…”
Section: Ellipsometrymentioning
confidence: 99%
“…24 The reverse transition from the cis to the trans conformation can either be induced thermally or by visible light. This reversible cis-trans photoisomerization process offers a wide range of applications 25 such as optical data storage, 26 optical switching, 27 polarization holography, 28 and the use of azobenzene functionalized molecules as a photolabile surfactants. 29 For this, azobenzene-based polymers and liquid crystalline polymers have been scrutinized intensively.…”
Section: ■ Introductionmentioning
confidence: 99%